2021
DOI: 10.3390/ma14174876
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Flow Model of Strain Hardening and Softening for Use in Tensile Testing of a Cylindrical Specimen at Room Temperature

Abstract: We develop a new flow model based on the Swift method, which is both versatile and accurate when used to describe flow stress in terms of strain hardening and damage softening. A practical issue associated with flow stress at room temperature is discussed in terms of tensile testing of a cylindrical specimen; we deal with both material identification and finite element predictions. The flow model has four major components, namely the stress before, at, and after the necking point and around fracture point. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In addition, the method can be used to reveal the material deformation behaviors even between fracture start point and fracture point [113], which is important to understand the fracture phenomena occurring in tensile test. Joun et al's approach also has a unique and important strong point, in that it can also be used to predict the flow behaviors during softening just before fracture [35]. However, the results are composed of a discrete flow information at the sample points of strain.…”
Section: The Experimental-numerical Combined Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the method can be used to reveal the material deformation behaviors even between fracture start point and fracture point [113], which is important to understand the fracture phenomena occurring in tensile test. Joun et al's approach also has a unique and important strong point, in that it can also be used to predict the flow behaviors during softening just before fracture [35]. However, the results are composed of a discrete flow information at the sample points of strain.…”
Section: The Experimental-numerical Combined Methodsmentioning
confidence: 99%
“…However, V 2 's of their results, i.e., 47.3 for Al6061-T4 and 855 for CP Ti, say that it is not an improved Voce model but an improved Swift model if we focused strictly on their motivation. Recently, Razali et al [35] proposed a modified Swift model to cope with the limitations of the traditional fundamental flow models.…”
Section: Extended Flow Models At Room Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additional flow constants should be used to solve this matter, which inevitably increases the complexity of finding the flow constants. Razali et al [ 34 ] added the second strain hardening parameter to the Swift model to cope with this matter. Its mathematical flexibility, however, is not acceptable and a smoothing function was thus assisted.…”
Section: Traditional Flow Models and Their Limitationsmentioning
confidence: 99%
“…In addition, Ludwik, Voce, and Swift models have another degree of freedom for satisfying the flow stress at a selected strain. In the previous study, [ 34 ] it was shown that it is very difficult to satisfy both pre‐ and postnecking strain hardenings at once using the only remained degree of freedom that the Ludwik, Voce, and Swift models have after satisfying the necking conditions. It is thus indispensable to use additional flow constants to satisfy their corresponding points additionally selected on the target flow curve, called the reference flow curve (RFC).…”
Section: Introductionmentioning
confidence: 99%